Robust full state tracking and ultimate exponential stabilization of nonholonomic wheeled mobile robots - Xu, Guangyan. (2008)
The object of this doctoral thesis is to develop novel theoretical results and practical techniques on the feedback control of nonholonomic wheeled mobile robots. Firstly, a brief review of previous work on the nonholonomic systems and their feedback control is provided. This is followed by the presentation of mathematical preliminaries used in the thesis.